The impact of intellectual property protection on the development of digital economy and regional entrepreneurial activity: Evidence from small and medium enterprises - Chen, Hong (Frontiers in Psychology, 2022)
The objective of this study was to understand the impact of intellectual property protection on the development of the digital economy and regional entrepreneurial activity in the context of SMEs. It is observed that open innovation is a key to the success of SMEs because it provides a way to work in the best way for getting a better opportunity for developing a competitive advantage in the target market. Furthermore, intellectual property management has a more critical responsibility to protect open innovation for commercialization performance and entrepreneurial performance. For this study, the data was collected by the management of SMEs on a five-point Likert scale questionnaire because the survey method is effective and cost-saving for collecting cross-sectional data. The results of this study conclude that the management must consider the critical role of intellectual property management for the protection of ideas shared in open innovation to get the performance in entrepreneurial functions of SMEs. This study provides significant implications for the effective moderating role of information communication technology and open innovation model constraints that would help the organization for the better productivity and commercialization performance of SMEs.